Synthesis of 3-(4-Hydroxy-3-Metoxyphenyil)-1-Phenyl-2-Propen-1-On and its Antioxidant Activity Assay using DPPH - Azizah, Yuzkiya; Hanapi, Ahmad; Adi, Tri Kustono (ALCHEMY, 2015)
ABSTRACT3-(4-hydroxy-3-methoxyphenyl)-1-phenylprop-2-en-1-one has been synthezed using aldol condensation reaction from vanillin. The research aims to incrase the potency of vanillin as antioxidant. The synthesis was carried out using reflux method at 70 °C for 1,5 hours at various moles between vanillin and acetophenone i.e. 1:1; 1:1,5; and 1,5:1. The products were characterized by TLC, FTIR, GC-MS and evaluated for their antioxidant potential using DPPH (2,2-diphenyl-1-picrylhydrazyl) assay. The best product was obtained by various moles between vanillin and acetophenone at 1:1,5 as a bright yellow solid with a melting point at 65 °C; 76.56 % yield; and 87.02 % purities, with IC50 of the product is 0.179 mM. Keywords: aldol condensation, antioxidant, vanillin